Derivation of vertical wavelengths of gravity waves in the MLT-region from multispectral airglow observations. (August 2018) - Schmidt, Carsten; Dunker, Tim; Lichtenstern, Sabrina; Scheer, Jürgen; Wüst, Sabine; Hoppe, Ulf-Peter; Bittner, Michael
Abstract: We present the derivation of gravity wave vertical wavelengths from OH airglow observations of different vibrational transitions. It utilizes small phase shifts regularly observed between the OH(3-1) and OH(4-2) intensities in the spectra of the GRIPS (GRound-based Infrared P-branch Spectrometer) instruments, which record the OH airglow emissions in the wavelength range from 1.5  μm to 1.6  μm simultaneously. These phase shifts are interpreted as being due to gravity waves passing through the OH airglow layer and affecting individual vibrational transitions at slightly different times due to small differences in their emission heights. The results are compared with co-located observations of the Na-Lidar measurements acquired between 2010 and 2014 at the Arctic Lidar Observatory for Middle Atmosphere Research (ALOMAR, 69.28° N, 16.01° E), Norway. This comparison shows best agreement if the mean height difference of the OH(3-1) and OH(4-2) emission is assumed to be 540 m (1σ = 160 m). The results are also compared with co-located observations of the OH(6-2)- and O2 b (0-1)-transitions by means of spectrometer observations (TANGOO instrument, Tilting-filter spectrometer for Atmospheric Nocturnal Ground-based Oxygen & hydrOxyl emission measurements) performed from 2013 until 2016 at Oberpfaffenhofen (48.08° N, 11.27° E), Germany. For approximately 40% of all wave events observed with GRIPS in the period range from 0.25 h to 17 h, a quantitative estimate of the phase relationship between the OH(3-1) and OH(4-2) intensities can be retrieved from the spectra allowing derivation of vertical wavelengths. The retrieval performs best for wave periods below two hours (80% success rate) and worse for periods above ten hours (successful in less than 10% of the cases). The average wavelength determined from 102 events amounts to 22.9 km (1σ: 9.0 km). The corresponding mean wavelength determined from the TANGOO observations amounts to 22.6 km ± 10.5 km, if a mean separation of 6.5 km is assumed for the height difference between the OH(6-2) and O2b(0-1)-transitions. Highlights: Small differences between individual OH Meinel bands in the airglow are investigated. The differences can be used to estimate vertical wavelengths of atmospheric waves. Independent observations of O2 airglow emissions support this view. The wavelengths are validated against co-located observations of a sodium lidar.